Capillary Deformations of Bendable Films - Cerda-Villablanca, E; Schroll, R (2013)
We address the partial wetting of liquid drops on ultrathin solid sheets resting on a deformable foundation. Considering the membrane limit of sheets that can relax compression through wrinkling at negligible energetic cost, we revisit the classical theory for the contact of liquid drops on solids. Our calculations and experiments show that the liquid-solid-vapor contact angle is modified from the Young angle, even though the elastic bulk modulus (E) of the sheet is so large that the ratio between the surface tension ? and E is of molecular size. This finding indicates a new elastocapillary phenomenon that stems from the high bendability of very thin elastic sheets rather than from material softness. We also show that the size of the wrinkle pattern that emerges in the sheet is fully predictable, thus resolving a puzzle in modeling "drop-on-a-floating-sheet" experiments and enabling a quantitative, calibration-free use of this setup for the metrology of ultrathin films. © 2013 American Physical Society.